Lack of latent tuberculosis (TB) screening and delay in anti-retroviral therapy initiation in HIV-TB co-infection: an 11-year study in an intermediate TB-burden country - Teng, Vannesa Yue May (2022)
Objectives: To examine the prevalence and characteristics of HIV-tuberculosis (TB) co-infected patients in Singapore, an intermediate TB-burden country.